If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4t + -5) + t = 40t Reorder the terms: 2(-5 + 4t) + t = 40t (-5 * 2 + 4t * 2) + t = 40t (-10 + 8t) + t = 40t Combine like terms: 8t + t = 9t -10 + 9t = 40t Solving -10 + 9t = 40t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-40t' to each side of the equation. -10 + 9t + -40t = 40t + -40t Combine like terms: 9t + -40t = -31t -10 + -31t = 40t + -40t Combine like terms: 40t + -40t = 0 -10 + -31t = 0 Add '10' to each side of the equation. -10 + 10 + -31t = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -31t = 0 + 10 -31t = 0 + 10 Combine like terms: 0 + 10 = 10 -31t = 10 Divide each side by '-31'. t = -0.3225806452 Simplifying t = -0.3225806452
| p(x)=23x^3+93x^2-111x-5 | | p(x)=23x^3 | | 6x+5-3=2 | | -2(t-1)+5t=7t-5 | | 4x+6x-16=3x+2x-26 | | 5x+y=62 | | 4(y-4)/5=-3y | | 6(6x-5)-5=36x-35 | | 0.04(y-4)+0.18y=0.02y-0.05(10) | | d(q-9)= | | 0.70x+0.35(100)=0.35(64) | | 0.50x+0.25(110)=0.25(40) | | 100*x=1.9247 | | -3(y-1)+2=4(y-3) | | z.16/2 | | -4-27=6y+13 | | x-2/3x | | 3.9(2x-1)+3.9x= | | -1.6(-3m+8)+2.3m= | | 2x+8x-4=x+768 | | 4-4y=9-5y | | r-2/3r | | 7x+2x+30=x+270 | | 8-(-3.4+6.45)= | | 8c+100=-12 | | 11-4x=(3x-2)(3x-2)+1 | | 7(x-2)+8=7x+3 | | (9f/2g)(4) | | -24=6+5w | | 50-3a=122 | | 12+8w=76 | | 36b^2-121= |